Odpowiedzi

2010-02-02T18:27:09+01:00
4x+5
a) 4*3+5=12+5=17
b) 4*(-3)+5=-12+5=-7

3x do kwadratu+2x=1

a)(3*10)^2+2*10=1
(30)^2+20=1
900+20=1
920=1
b)[3*(-2)]^2+2*(-2)=1
(-6)^2-4=1
36-4=1
32=1

5xdo kwadratu-y

a) (5*3)^2-(-3)
(15)^2+3
225+3=228

2a do kwadratu-b do kwadratu
a)2*(-1)^2-(-1)^2
2*1-1
2-1=1

b)2*(1)^2-(1)^2
2*1-1
2-1=1

^2 to kwadrat jak coś :)
2010-02-02T18:32:52+01:00
A) 4x+5=4×3+5=12+5=17
a*x=3
b) 4x+5=4×(-3)+5=-12+5=-7
b=x-3

a) 3x²+2x=1
3×10²+2×10=1
3×100+20=1
320=1
a*x=10

b) 3x²+2x=1
3×(-2)²+2×(-2)=1
3×4-4=1
12-4=1
8=1
b*x=-2

5x²-y
5×3²+3
5×9+3
45+3
48
a=x=3,y=-3

a) 2a²-b²
2×(-1)²+1²
2×1+1
2+1
3
a*a=-1,b=-1

2a²-b²
2×1²-1²
2×1-1
2-1
1
b*a=1,b=1
proszę o dokładne rozwiązanie.